The Effectiveness of The Academic Supervision Model in Encouraging The Professionalism of Elementary School Teachers in Ungaran Timur District - Zulianti Lisa Kurniawati; AY Soegeng Ysh; Ngurah Ayu Nyoman Murniati (Journal of Educational Sciences, 2026)
Teacher professionalism is highly needed in today's era. Teacher professionalism will be seen from teachers' efforts to improve qualifications, certification, competency, and adapt to changes in the work environment. This study aims to analyze and measure the effectiveness of the implementation of an academic supervision model in an effort to improve the professionalism of public elementary school teachers in East Ungaran Regency. This study uses a quantitative ex post facto approach, involving public elementary school teachers in East Ungaran Regency as subjects. Data were collected through instruments that measure the quality of academic supervision and the level of teacher professionalism, then analyzed using regression and correlation techniques to determine the relationship and influence between variables. The results show that the effectiveness of the academic supervision model is in the high category and has an important role in improving teacher quality. Statistically, academic supervision is a strong and significant predictor in improving the professionalism of elementary school teachers in the region. These findings have important implications for regional education policy, particularly in determining the priorities of supervision programs, the focus of improving teacher professionalism, and the development of supervisor capabilities and competencies.